2022
DOI: 10.3389/fcvm.2022.895609
|View full text |Cite
|
Sign up to set email alerts
|

Association Between a Novel Metabolic Score for Insulin Resistance and Mortality in People With Diabetes

Abstract: BackgroundGrowing studies have shown that insulin resistance (IR) is associated with poor prognoses among patients with diabetes, whereas the association between IR and mortality has not been determined. Hence we aimed to evaluate the associations between IR and all-cause, cardiovascular diseases (CVDs) and cancer-related mortality in patients with diabetes.MethodsWe enrolled 2,542 participants with diabetes with an average age of 57.12 ± 0.39 years and 52.8% men from the 1999–2014 National Health and Nutritio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 57 publications
2
9
1
Order By: Relevance
“…Additionally, we found that the METS‐IR index was strongly correlated with the risk of all‐cause death and diabetes among individuals without diabetes, which is in agreement with previous studies 40,41 . A recent study 42 showed that METS‐IR was nonlinearly associated with all‐cause mortality and CVD‐related mortality in patients with diabetes, which is consistent with our findings because, in our study, the number of all‐cause and CVD deaths in the individuals with diabetes also increased with the elevation of METS‐IR, although this change was not statistically significant due to the lower event number. It is noteworthy that a linear relationship between METS‐IR levels and MACEs was observed in individuals with diabetes, whereas a nonlinear relationship was observed in those without diabetes.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, we found that the METS‐IR index was strongly correlated with the risk of all‐cause death and diabetes among individuals without diabetes, which is in agreement with previous studies 40,41 . A recent study 42 showed that METS‐IR was nonlinearly associated with all‐cause mortality and CVD‐related mortality in patients with diabetes, which is consistent with our findings because, in our study, the number of all‐cause and CVD deaths in the individuals with diabetes also increased with the elevation of METS‐IR, although this change was not statistically significant due to the lower event number. It is noteworthy that a linear relationship between METS‐IR levels and MACEs was observed in individuals with diabetes, whereas a nonlinear relationship was observed in those without diabetes.…”
Section: Discussionsupporting
confidence: 93%
“…Given these points, it can be inferred that higher IR may lead to increased mortality related to cancer and CVD. Some studies have yielded diverse results regarding the correlation between IR and mortality, encompassing both all-cause and cause-specific outcomes ( 27 , 44 53 ). When interpreting our results within the context of previous research, both concordant and discordant findings emerge.…”
Section: Discussionmentioning
confidence: 99%
“…In the analysis of the association between IR and cause-specific mortality, no study demonstrated a significant association with both cancer-related and CVD-related mortality. Some studies established an association between IR and all-cause mortality ( 44 , 45 ), along with either CVD ( 27 , 46 49 ) or cancer-related mortality ( 50 , 51 ), while others failed to find associations with mortality ( 52 , 53 ). This implies that understanding the shared pathophysiology, such as insulin resistance, between CVD and cancer, while simultaneously comprehending the distinct characteristics of each disease, is crucial for formulating tailored strategies for each.…”
Section: Discussionmentioning
confidence: 99%
“…The hyperinsulinemic-euglycemic clamp is recognized as the gold standard for evaluating IR, but due to the relatively complicated measurement method, it cannot be widely used in large-scale epidemiological investigations; While MetS-IR, as a simple IR surrogate indicator, is considered to be widely used (16). The MetS-IR is a new score to assess cardiometabolic risk in healthy and high-risk subjects and a promising tool to screen for insulin sensitivity, as described by Bello-ChavollaOY et al The value of this parameter has been confirmed in a large number of subsequent epidemiological investigations, including risk assessment and prediction of diabetes, NAFLD, hyperuricemia, prehypertension, and hypertension, hypertension combined with hyperuricemia, metabolic syndrome, and various chronic diseaserelated complications (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)40). Also, it is worth noting that in a recent study by Li et al, who included 1,205 baseline normoglycemic subjects and evaluated the association between MetS-IR and prediabetes for the first time, their results showed that, MetS-IR was not significantly associated with prediabetes (17).…”
Section: Discussionmentioning
confidence: 99%